Risk knowledge sharing, risk management culture and enterprise risk management implementation in the Nigerian financial industry - Ahmed, Idris; Abdul Manab, Norlida (2016)
This study has investigated the Influence of risk knowledge sharing and risk management culture on ERM framework implementation in the Nigerian financial industry among 47 firms.Questionnaires were administered to those in charge with risk management practices such as chief risk officers and other senior level managers of the sampled firms.The study utilized PLS-SEM causal modelling with the aid of SmartPLS 2.0 program software to test the hypotheses.The results of the analysis indicated that risk knowledge sharing and risk management culture have significant positive effect on ERM framework implementation in the Nigerian financial industry.The study recommended the need for firms in Nigeria to deploy more resources to entrench sound risk culture and knowledge management techniques (such as risk knowledge sharing) to improve their risk management practices.The practical implication of the research has been discussed.